Lipids as biomarkers of brain disorders. Issue 3 (4th February 2020) - Hussain, Ghulam; Anwar, Haseeb; Rasul, Azhar; Imran, Ali; Qasim, Muhammad; Zafar, Shamaila; Imran, Muhammad; Kamran, Syed Kashif Shahid; Aziz, Nimra; Razzaq, Aroona; Ahmad, Waseem; Shabbir, Asghar; et al.
Abstract: Brain is a central and pivotal organ of human body containing the highest lipids content next to adipose tissue. It works as a monitor for the whole body and needs an adequate supply of energy to maintain its physiological activities. This high demand of energy in the brain is chiefly maintained by the lipids along with its reservoirs. Thus, the lipid metabolism is also an important for the proper development and function of the brain. Being a prominent part of the brain, lipids play a vast number of physiological activities within the brain starting from the structural development, impulse conduction, insulation, neurogenesis, synaptogenesis, myelin sheath formation and finally to act as the signaling molecules. Interestingly, lipids bilayer also maintains the structural integrity for the physiological functions of protein. Thus, in light to all of these activities, lipids and its metabolism can be attributed pivotal for brain health and its activities. Decisively, the impaired/altered metabolism of lipids and its intermediates puts forward a key step in the progression of different brain ailments including neurodegenerative, neurological and neuropsychiatry disorders. Depending on their associated underlying pathways, they serve as the potential biomarkers of these disorders and are considered as necessary diagnostic tools. The present review discusses the role and level of altered lipids metabolism in brain diseases including neurodegenerative diseases, neurological diseases, and neuropsychiatric diseases. Moreover, the possible mechanisms of altered level of lipids and their metabolites have also been discussed in detail.